Poetic Industry and Abominable Superstition: Southey on Lope de Vega - González, Jonathan (Romanticism on the Net)

(untitled) (Université de Montréal, 2017)
In the second edition of Joan of Arc (1798) and in Roderick, The Last of the Goths (1814), Robert Southey included explanatory notes that featured excerpts from Lope de Vega’s Jerusalén conquistada (1609), an epic poem in twenty cantos based on Torquato Tasso’s Gerusalemme liberata (1581) and built around a mythified account of the Third Crusade. This article argues that, rather than being offhand allusions, those references lie at the core of a deeper literary, religious, and political interest in the figure and writings of the sixteenth-century Spanish writer. Southey’s contribution to the criticism of the so-called “Phoenix of Wits” might be difficult to assess, not least because in a period of over twenty years he went from asserting that “Lope de Vega is never sublime, seldom pathetic, and seldom natural” (CLRS 188) in a series of public letters he contributed to the Monthly Magazine in 1796, to becoming a true aficionado of this “prodigy of nature,” in 1818 celebrating his Rimas sacras (1599) as being characterised by “strains of sober piety and elevated devotion, in which a true Christian might devoutly join, and bless the man who has expressed for him so well the aspirations of hope and faith” (QR 45). Southey’s ambivalent cultural cosmopolitanism, nevertheless, meant that even when he celebrated Lope de Vega’s poetic industry, he was balanced in his praise, leaving room for harsh attacks on the “audacious instances of Romish impiety and imposture” in the Spaniard’s oeuvre (QR 44). Southey’s ambivalence towards Lope de Vega is read here in the light of his investments in all things Spanish, considering the public and private, domestic and international dimensions of his writings, and arguing that his fixation with Lope de Vega epitomises what Lynda Pratt (Contexts xxvi) has defined as the Southeyan preoccupation with a foreign “Other” that is both fascinating and repulsive.